Clinical outcomes of thirteen patients with acute chagas disease acquired through oral transmission from two urban outbreaks in northeastern Brazil. - Claudilson J C Bastos; Roque Aras; Gildo Mota; Francisco Reis; Juarez Pereira Dias; Robson Silva de Jesus; Miralba Silva Freire; Eline G de Araújo; Juliana Prazeres; Maria Fernanda Rios Grassi (Public Library of Science (PLoS), 2010)
Background Outbreaks of orally transmitted Trypanosoma cruzi continue to be reported in Brazil and are associated with a high mortality rate, mainly due to myocarditis. Methods This study is a detailed report on the disease progression of acute Chagas disease in 13 patients who were infected during two micro-outbreaks in two northeastern Brazilian towns. Clinical outcomes as well as EKG and ECHO results are described, both before and after benznidazole treatment. Results Fever and dyspnea were the most frequent symptoms observed. Other clinical findings included myalgia, periorbital edema, headache and systolic murmur. Two patients died of cardiac failure before receiving benznidazole treatment. EKG and ECHO findings frequently showed a disturbance in ventricular repolarization and pericardial effusion. Ventricular dysfunction (ejection fraction <55%) was present in 27.3% of patients. After treatment, EKG readings normalized in 91.7% of patients. Ventricular repolarization abnormalities persisted in 50% of the patients, while sinus bradycardia was observed in 18%. The systolic ejection fraction normalized in two out of three patients with initially depressed ventricular function, while pericardial effusion disappeared. Conclusions Myocarditis is frequently found and potentially severe in patients with acute Chagas disease. Benznidazole treatment may improve clinical symptoms, as well as EKG and ECHO findings.